The nymph of Gilliesia Peters & Edmunds, 1970 (Ephemeroptera: Leptophlebiidae), with description of a new species from Thailand - Boonsoong, Boonsatien; Sartori, Michel (Zootaxa, 2015)
The new species Gilliesia ratchaburiensis sp. nov. is described based on male and female imagos (some of them reared from nymphal stages), nymphs and eggs collected in western Thailand. The nymph of Gilliesia, which is described for the first time, has bifid gills, a dense patch of setae on the ventral side of the glossae, no posterolateral spines on abdominal segment VIII, maxillary palpi 3-segmented and very reduced maxillary canines. Compared to congeners, the male imagos of the new species have penis lobes more straight and with the apical portion bent laterally but not ventrally, and female abdominal sternum 9 with a U-shaped, deep, median cleft. Phylogenetically, Gilliesia seems to be more similar to Dipterophlebiodes than to Habrophlebiodes and other Leptophlebiinae. The present finding in Thailand expands the distribution of Gilliesia in tropical Southeast Asia.